O processo judicial eletrônico como meio de efetivação do acesso à justiça para concretização dos direitos trabalhistas - Nabarreto, Rodrigo Lopes (2014)
The present study aims to evaluate the electronic judicial proceedings of the Labor Court from the perspective of access to justice and efficiency. Starts analyzing the evolution of the law and the state. Invokes the theory of objective dimension of fundamental rights as motivator of the creation of the electronic judicial process that follows a retelling of the current legal system. After it is evaluated the development of the legal provision of technology use in the Judiciary. Then presents the data collected from field research conducted in the Second Labour Court in Guarulhos member of the Regional Labor Court of São Paulo. Finally, it is concluded that, effectively, the Judicial Process Electronic caused a paradigm shift, generating greater effectiveness to the principles of access to justice and efficiency. The research made use of the hypothetical deductive method with the technique of literature and the inductive method with respect to the field research. Was used as the main theoretical framework Daniel Sarmento.